2014
DOI: 10.1111/1469-0691.12452
|View full text |Cite
|
Sign up to set email alerts
|

Population structure analyses of Staphylococcus aureus at Tygerberg Hospital, South Africa, reveals a diverse population, a high prevalence of Panton–Valentine leukocidin genes, and unique local methicillin-resistant S. aureus clones

Abstract: Studies reporting on the population structure of Staphylococcus aureus in South Africa have focused only on methicillin-resistant S. aureus (MRSA). This study describes the population structure of S. aureus, including methicillin-susceptible S. aureus (MSSA) isolated from patients at Tygerberg Academic Hospital, Western Cape province. Pulsed-field gel electrophoresis (PFGE), detection of Panton-Valentine leukocidin (PVL), spa typing, multilocus sequence typing (MLST), agr typing and SCCmec typing were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 28 publications
8
25
0
Order By: Relevance
“…This is in stark contrast to Europe, where the prevalence of PVL‐positive isolates is low (0.9–1.4%) . Studies from Gabon and South Africa further support the association of PVL with abscesses and skin and soft tissue infection . The reasons for the high prevalence of PVL are unknown, but might be related to the host (i.e.…”
Section: Epidemiology Of S Aureus Colonizationmentioning
confidence: 89%
See 1 more Smart Citation
“…This is in stark contrast to Europe, where the prevalence of PVL‐positive isolates is low (0.9–1.4%) . Studies from Gabon and South Africa further support the association of PVL with abscesses and skin and soft tissue infection . The reasons for the high prevalence of PVL are unknown, but might be related to the host (i.e.…”
Section: Epidemiology Of S Aureus Colonizationmentioning
confidence: 89%
“…Distribution of methicillin‐resistant S taphylococcus aureus ( MRSA ) clones in Africa. The three major MRSA multilocus sequence types ( ST s) of each study were identified . Of these, the five most widely distributed clones in A frica are shown.…”
Section: Population Structurementioning
confidence: 99%
“…The majority of the bovine isolates collected from this site were ST352; no other S. aureus ST8 isolates were detected. Staphylococcus aureus ST8 has been reported extensively from human carriage and clinical specimens (Sakwinska et al, 2009; Oosthuysen et al, 2014). This lineage also comprises a number of significant MRSA clones (Monecke et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SCCmec type IV was found in twice as many MRSA clones as other SCCmec types, suggesting that most clones arise by acquisition of SCCmec type IV by S. aureus [90]. This is probably a result of the smaller size of SCCmec type IV compared with other SCCmec types, which may facilitate transfer of the cassette among staphylococcal species [98]. Furthermore, it has been shown that MRSA strains that belong to the major CCs (1,5,8,22,30,45) are easier to transform with mecA-expressing plasmids tan are strains belonging to minor CCs.…”
Section: Staphylococcus Aureusmentioning
confidence: 99%
“…This spread from Europe to the USA [54]. In Africa the presence of the following clones: sequence type (ST) 5-MRSA-I, ST239-MRSA-III, ST612-MRSA-IV, ST36-MRSA-II and ST22-MRSA-IV have been reported [97,98]. ST239 is also common in mainland Asia, South America and parts of Eastern Europe [54].…”
Section: Epidemiology Of Methicillin-resistant S Aureusmentioning
confidence: 99%